Sex estimation from the navicular bone in Spanish contemporary skeletal collections. (October 2016) - Saldías, Eduardo; Malgosa, Assumpció; Jordana, Xavier; Isidro, Albert
Highlights: Using navicular's measurements, sexual dimorphism in Spanish population was found. Through the ROC curve and logistic regressions, we obtained >80% of correct accuracy. Navicular bone is a good option to determine sex because of its high accuracy and longer preservation time. Abstract: Sexual estimation is fundamental to reconstruct the biological profile of individuals, but postdepositional factors can alter the resistance of the bones, thereby preventing accurate diagnosis especially when the skull and the pelvis are absent. Navicular bones are usually well preserved in archeological and forensic contexts and can a good alternative to discriminate sex. On the basis of these aspects, the present investigation analyzed the sexual dimorphism in 231 pairs of navicular bones from documented contemporary collections from Spain. Receiver operating characteristic (ROC) curve analysis and binary logistic regressions were carried out in eight replicable linear measurements of the navicular bone. Each of the eight variables showed a significant sexual dimorphism in our sample. The ROC curve results indicate that at least five out of the eight variables used have high ability for sex diagnosis, among which the maximum length of the cuneiform surface (LMAXCUN) showed a better performance (area under the curve value = 0.86). Moreover, we introduced regression equations with combination of measurements that correctly allocated the skeletons with 80% or greater accuracy. The equation with high allocation accuracy rate (83.4%) included a combination of the maximum height of the navicular (HMAX), maximum length of the cuneiform surface (LMAXCUN), and maximum length of the talar facet (LMAXTAL). The regression equations presented here are useful for the Western Mediterranean populations and offer better alternatives than formulas based on other population groups.